Africanizing of the English language in African Novels: Analysis of Abdulrazack Gurnah's Afterlives (2020) - Kazinja, Geniva; Xu, Shiyan (International Journal of Linguistics, 2023)
Purpose: This article aimed to ascertain which methods were used to Africanize the language used in Gurnah's Afterlives. It is well known that Abdulrazack was born and raised in Tanzania (Africa), and how to be an African was reflected in his work through language was the main aim of this article. Unfortunately, studies on Africanizing English language in African novels are few and based on old novels. Therefore, researchers need to analyze the current works written in English by Africans to find out which methods were used to Africanize English in their works. Methodology: This research used a descriptive qualitative method. It means that it describes the method used in Gurnah's Afterlives to Africanize the English language based on the data gained through reading the whole content of the novel. This article was grounded on the Languages in Contact theory introduced by Uriel Weinreich's languages in Contact: Findings and Problems (1953). Data were analyzed by using a content analysis-directed approach. Findings: It was found that Gurnah used code-mixing, code-switching, and translation to Africanize English Language. Furthermore, the main reason was to reflect on the language used in daily activities in Tanzanian society. Unique Contribution To Theory, Practice and Policy: This article contributes to the theory that, not only in spoken language where we can notice languages in contact, but also in literary works where the writers reflect on how the certain society use language in daily activities. Thus, even though the writer chooses to write in another language, we can still notice the characteristics of his language in his writing, as shown in Gurnah's Afterlives novels.